Nutrition services by health providers during antenatal consultations in Senegal: a comparison of observed versus self-reported practices - Elhadji Alioune Badara Ningue; Isabelle Galibois; Sonia Blaney (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Malnutrition is of concern among pregnant women in Senegal. This paper aimed to compare health providers' self-reported practices to their actual provision of nutrition services during antenatal care (ANC) consultations. # Methods A comparative study was conducted in a random sample of 27 health providers in the Kolda region. Two ANC consultations were monitored for each provider, and later compared to the data that were collected through a face-to-face interview. This provided us with the opportunity to assess the agreement between self-reported and observed actions namely clinical actions, verbal assessments and counseling. # Results In general, the ANC providers reported similar extent of clinical actions that they performed. However, in verbal assessments, health providers over-reported inquiring about iron and folic acid intake (44% observed vs 89% reported) and its potential side effects (0% vs 33%), signs of vitamin A deficiency (0% vs 11%) and intake of parasite prophylaxis (18% vs 63%). They also over-reported the provision of counseling on the importance of avoiding tea/coffee (41% observed vs 74% reported), gaining appropriate weight (14% vs 44%), and eating specific foods (7% vs 52%). # Conclusions Nutrition services during ANC should be improved, especially in the domains of verbal assessment and nutrition counseling. The possible causes of these discrepancies might be the time constraint for ANC, limited skills, or a low demand of pregnant women for nutritional guidance. Nutrition training and/or supportive supervision of health providers deserve more attention in order to improve the nutrition services and the overall quality of ANC.